Boundary Regularity and Some Convergence Results for p-harmonic Functions on Metric Spaces - Dr. Zohra Farnana (Aljameai, 2022)
abstract:Let     be a complete metric space equipped a doubling Borel measure supporting the p-Poincar  inequality.  In this paper, we discuss the results of a study on the regularity of -harmonic functions at the boundary points. In particular, we show that the -harmonic functions attain their boundary values at all regular boundary points. Moreover, the set of irregular points is a small set. We also show that the uniform limit of -harmonic functions is   -harmonic. In addition, we obtain various convergence results for the - harmonic functions with fixed boundary data, on an increasing sequence of open sets.الملخص:في هذا البحث ندرس استمرارية الدوال التوافقية عند النقاط الحدية  في الفضاءات المترية. بالأخص  نبين ان الدوال التوافقية مستمرة عند كل النقاط الحدية المنتظمة وان مجموعة النقاط الحدية الغير منتظمة مجموعة صغيرة.  كذلك ندرس بعض مسائل التقارب حيث نبين ان التقارب المنتظم للدوال التوافقية هو أيضا دالة توافقية. بالإضافة الى دراسة بعض مسائل التقارب للدوال التوافقية على مجموعات مفتوحة متداخلة